Rethinking lithium-ion battery management: Eliminating routine cell balancing enhances hazardous fault detection. (July 2023) - Hardy, John; Steggall, John; Hardy, Peter
Abstract: Current battery management systems for lithium-ion battery packs incorporate circuitry and software to carry out routine voltage balancing of cells in order to optimise battery performance by preventing the state of charge of individual cells drifting apart over time. Drawing on evidence from previous published research, this paper reports experimental results testing the hypothesis that routine balancing can be successfully eliminated over a battery's lifetime. The test method requires that specified steps are taken to prepare the cells and that a novel charging protocol is employed thereafter to ensure the pack is fully charged while accommodating cell-to-cell variations in capacity, aging and dynamic response. Extensive cycle testing on a range of different battery configurations found no evidence of loss of balance and hence of reduction in lifetime battery performance compared to conventional battery management systems incorporating routine dissipative balancing. Importantly, the experiments also found that elimination of routine balancing greatly enhances the scope for early detection of low-level self-discharge caused by developing internal short circuits. Internal short circuits are implicated in occasional highly destructive spontaneous battery thermal runaway events which have hitherto proved very difficult to predict when using conventional cell voltage balancing systems. The described method of battery management thus offers significant potential, especially for applications where the risk of sudden battery fires cannot be tolerated. In addition, the absence of high voltage balancing wires may bring other benefits, including simplified battery assembly, safer maintenance and reduced risk of hazardous wiring faults. Graphical abstract: Unlabelled Image Highlights: Experiments on cycling series-connected lithium batteries without routine balancing Novel charge algorithm ensures effective charging even with non-uniform cells. Comparison with routine balancing shows favourable results over lifetime cycling. Omission of cell balancing enables sensitive cell internal short circuit detection. The described method has significant potential for all safety-critical applications.